Calcio, soggettività e immaginari nell’esperienza dei “minori non accompagnati” - Anna Elia; Valentina Fedele (Culture e Studi del Sociale)
Based on a qualitative research that has involved young migrants belonging to the normative category of unaccompanied minors according to the Italian Law, hosted in centres of the Sistema di Accoglienza Integrato (SAI- Integrated Reception System), the article questions the role of football in young migrants’ daily life. Football, indeed, both played and enjoyed as a “fan”, being outside the normed paths of integration, is a possible space for the expression and affirmation of migrant subjectivities, where specific paths of construction of self-esteem can be activated. Within these paths, an important role is given to those models of masculinity that are built in the football imaginary, whose articulation allows to grasp the specific gender dimension of young migrants’ biographical experience.